Fenologia e artrópodes de Copaifera langsdorffii Desf. no cerrado - Almeida, C. I M [UNESP]; Leite, G. L D; Rocha, S. L.; Machado, M. M L; Maldonado, W. C H (My University, 2006)
There was evaluated the phenology and arthropods as well as the effect of weather on copaiba (Copaifera langsdorffii Desf.) (Leguminoseae). The emission of new leaves and inflorescences as well as the opening of them occurred in the rainy period. There were observed the higher diversity and abundance of insects, principally galling insects.
Phenology and arthropods of Copaifera langsdorffii in the cerrado (Brazilian Savannah)
Keywords: Copaiba; Insect galls; Parasitoids; Weather factors; arthropod; biodiversity; Brazil; controlled study; Copaifera langsdorffii; inflorescence; insect; legume; nonhuman; phenology; plant leaf; savanna; scrub; weather; Arthropoda; Hexapoda; Insecta